Effects of Pneumococcal Vaccination in Children Under Five Years of Age in the Democratic Republic of Congo: A Systematic Review - Marcellin Mengouo Nimpa; Abel Ntambue; Christian Ngandu; M. Carolina Danovaro-Holliday; André Bita Fouda; Aimé Mwana-Wabene Cikomola; Jean-Crispin Mukendi; Dieudonné Mwamba; Adèle Daleke Lisi Aluma; Moise Désiré Yapi; Jean Baptiste Nikiema; Boureima Hama Sambo; et al. (Vaccines)
Background: In the Democratic Republic of Congo (DRC), the 13-valent pneumococcal conjugate vaccine (PCV13) was introduced in 2011 through a three-dose schedule, targeting infants as part of the Expanded Program on Immunization (EPI), to reduce pneumococcal-related morbidity and mortality. The aim of this study was to determine the proportion of pneumonia and meningitis cases and deaths prevented in children under five following the introduction of this vaccine. Methods: This is a systematic review. We synthesized findings from studies carried out in the DRC between 2011 and 2023. We searched scientific articles, published and unpublished doctoral theses and conference proceedings. Only papers written in French or English and those reporting the results of original analytical studies were selected. We assessed the direct effect of PCV13 by calculating the proportion of infections avoided, using Odds Ratios or prevalence ratios related to infection or pneumococcal carriage. Results: Four studies were included in this review. Regarding pneumococcal carriage, when children received three PCV13 doses, the prevalence of carriage was reduced by 93.3% (95% CI: 86.3 to 96.6%), while a single dose did not significantly reduce the prevalence of carriage compared with children who had not received any dose. Concerning pneumonia prevention, three doses of PCV13 prevented 66.7% (95% CI: 37.2 to 82.2) of cases among vaccinated children. The proportion of meningitis attributable to S. pneumoniae prevented was 75.0% (95% CI: 6% to 93.3%) among children vaccinated with PCV13. S. pneumoniae serotypes 19F and 23F were the most frequent causes of invasive pneumonia in children. Serotypes 35B/35C, 15B/C, 10A and 11A/D were the most frequently identified causes of morbidity in Congolese children. In 2022, with PCV13 vaccination coverage at 79.0%, an estimated 113,359 cases of severe pneumonia and 17,255 pneumonia-related deaths were prevented in the DRC, with 3313 cases and 1544 deaths attributable to pneumococcal meningitis prevented. Conclusions: There is clear, but scattered, evidence of reduced colonization by S. pneumoniae and hospital admissions due to pneumococcal pneumonia and meningitis. The results also show that S. pneumoniae serotypes 35B/35C, 15B/C, 10A and 11A/D not included in PCV13 were the main cause of pneumococcal disease in unvaccinated or under-vaccinated children. These data support the need to continue improving vaccination coverage among children who are unvaccinated or incompletely vaccinated with PCV13 to reduce the burden of pneumococcal infections in the DRC.